Description of a new species of Neorhinotora Lopes, 1934 (Diptera: Heleomyzidae) from Central America - Menezes, Isis Sá; Calhau, Julia; Ale-Rocha, Rosaly (Zootaxa, 2021)
A new species of Neorhinotora Lopes, 1934 (Diptera, Heleomyzidae) is described: Neorhinotora elsalvadorensis sp. nov., from El Salvador, Central America, with illustrations of external and internal morphological characters and update of the identification key.